Civil liability of private security: Enforcer of moral obligations to right legal wrongs - Moore, Richter H. (American journal of criminal justice, 1987)
The private security industry in the United States now has approximately twice as many personnel as does the public police. Private Security personnel have authority over the liberty, and sometimes the lives, of customers and employees. Often they exercise this awesome responsibility with little if any background and training. In most instances private security personnel are not considered law officers or peace officers and are, therefore, not bound by the same rules and regulations that apply to public police. More and more frequently, untrained or minimally trained, and basically unqualified security officers are taking actions against customers and employees which are excessive and unreasonable. Without the Constitutional protections which would be available if the act were committed by a public police officer, the only recourse for a private individual against reckless and wanton conduct on the part of private security personnel is a civil action, seeking compensation for the inconvenience caused or injuries received. The courts have found that companies and their security personnel have an obligation to be reasonable in their investigations of suspected criminal violations by employees and customers. Failure to conduct a proper and reasonable investigation will open the individual directing the investigation, and the company authorizing it, to liabililty for the injury their improper actions have caused. Civil liability suits have become the moral enforcer for improper and excessive conduct by private security personnel.